Analisis Determinan Beberapa Variabel Terhadap Gross National Income Per Kapita Indonesia Tahun 2003-2022 - Pramana, I Made Bayu; Meydianawathi, Luh Gede (Jurnal Sosial Teknologi, 2025)
Economic growth is the main indicator of a country's ability to produce goods and services, measured by the increase in Gross Domestic Product (GDP) and Gross National Income (GNI) in a certain period. GDP reflects the value of domestic production of goods and services, while GNI measures the total income received by the population, including from abroad. Both indicators are important for assessing people's welfare, where GNI per capita is often used to compare prosperity between countries. Indonesia is projected to have great potential for economic growth and could even become the world's fourth largest economy by 2045, supported by a demographic bonus that increases the number of productive-age population. However, to achieve this potential, Indonesia must overcome the middle-income trap and optimally utilize the demographic advantage by improving the quality of human resources and appropriate economic policies. This study analyzes the effect of Foreign Direct Investment (FDI), Human Capital Index (HCI), Government Effectiveness Index, and Labor Force Participation Rate (TPAK) on GNI per capita in Indonesia. The study uses a quantitative descriptive method with the Ordinary Least Squares (OLS) approach to determine the effect of independent variables simultaneously and partially on the dependent variable. The results of the study show that FDI and HCI have a significant effect on GNI per capita, while government effectiveness and labor force participation have no significant effect. This model explains 94.5% of the variation in GNI per capita through the variables studied. The implications of this study emphasize the importance of increasing foreign investment and the quality of human resources, as well as the need for government policies that focus on investment incentives, strengthening education, and job training to encourage sustainable economic growth.